2011
DOI: 10.1097/rhu.0b013e318204a6f8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Subclinical Enthesopathy in Patients With Spondyloarthropathy

Abstract: The present study demonstrates a higher sensitivity of ultrasound with respect to physical examination in the detection of signs indicative of enthesopathy in SpA patients with an adequate interreader and intrareader reliability. Further study is needed about the prognostic value of the ultrasound findings for predicting clinical onset of entheseal involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 30 publications
0
16
0
2
Order By: Relevance
“…However, the involvement of entheseal-related structures is not always specific to SpA and may be observed in other noninflammatory and traumatic conditions with enthesis involvement (1)(2)(3)(4). Therefore, to differentiate the origin of the pathologic process, the term enthesopathy is commonly used to describe a metabolic or degenerative/ traumatic cause, whereas the term enthesitis refers to an inflammatory cause, such as in SpA (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the involvement of entheseal-related structures is not always specific to SpA and may be observed in other noninflammatory and traumatic conditions with enthesis involvement (1)(2)(3)(4). Therefore, to differentiate the origin of the pathologic process, the term enthesopathy is commonly used to describe a metabolic or degenerative/ traumatic cause, whereas the term enthesitis refers to an inflammatory cause, such as in SpA (1)(2)(3)(4).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to differentiate the origin of the pathologic process, the term enthesopathy is commonly used to describe a metabolic or degenerative/ traumatic cause, whereas the term enthesitis refers to an inflammatory cause, such as in SpA (1)(2)(3)(4). However, the 2 terminologies have often been used interchangeably in studies published in the literature, which has led a group of researchers to develop the concept of the enthesis organ, despite the origin (5).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is consistent evidence supporting the higher sensitivity over clinical examination of US in the diagnosis of enthesitis [55][56][57][58] (Fig. 2A).…”
Section: Detection Of Inflammatory Processmentioning
confidence: 65%
“…32,33 USG has the ability to detect subclinical enthesitis in SpA patients and it may be superior to clinical examination alone in detecting enthesitis. 34 Interestingly, a recent study showed the role of USG in nail imaging in patients with psoriasis and psoriatic arthritis, especially the abnormalities of the ventral plate and the difference between the mean distance ventral plate-osseous margins of the distal phalanx in this patient group. 35 Some of the USG features of Spa have been illustrated in Fig.…”
Section: Spondyloarthropathiesmentioning
confidence: 87%